Design And Modelling of Toroidal Inductors with Different Geometries for a Single-Phase Inverter Application - Quinn, Raymond; Vesa, Joonas; Rasilo, Paavo (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
The prevalence of power electronic converters is increasing as part of the transition to renewable energy and electric transportation. One obstacle in improving the power density of converters is the size and mass of the electromagnetic components used in these devices. Fast and accurate design and modelling tools are required to optimise and reduce the footprint of electromagnetic components. This paper introduces a new approach based on the area-product method for rapidly designing inductors with different geometries. The behaviour of the designed inductors is simulated using a MATLAB Simulink model for laminated magnetic cores. The simulation results are presented and discussed.